How can simulation help raise awareness of challenges related to medication management in nursing homes? - Opheim, Helene Margrethe Storebø; Arntzen, Kari; Larsen, Kristian (Nordisk Tidsskrift for Helseforskning, 2023)
Background: Simulation is an educational method that can be used to clarify complex issues. Challenges related to medication management in various healthcare facilities including nursing homes are known. We wanted to see if simulation could be useful to bring out different challenges that are associated with this area. The purpose of this article is to describe nurses' and health care assistants' experiences of participating in simulation, and what reflections arise around medication management in nursing homes. Method: Qualitative method with focus group interviews. Results: Nurses and health care assistants became aware of various challenges related to medication management using simulation. Most of them experienced the simulation as a useful method in raising awareness. Most of them felt that they learned something that gave new insight into their own work situation. There were challenges related to distractions and stress, a shortage of nurses as well as unclear responsibilities and task distributions. Conclusion: Simulation as a method can be awareness-raising in order to visualize various challenges related to medication management in nursing homes.
Keywords: nursing home; medication management; nurses; health care assistants; simulation